Itinerant Bubbles: hybrid carnival security and privatisation of public spaces - Oliveira, Pedro (International journal of comparative and applied criminal justice, 2022)
Several authors have stated that the performance of private security firms in public spaces fosters privatisation and the exclusion from these spaces of users who are considered inopportune or undesirable. This study examines the hypothesis that these negative impacts are maximised by the intermingling or hybridism between such companies and the police forces. It analyzes the influence of this hybridism on the security model and the tactics adopted by the organised groups of revellers or roped-off blocos that parade during Carnival. It argues that this hybrid security make use of coercive and confrontational tactics to ensure the wellbeing and safety of member revellers, while barring non-paying revellers’ access to the blocos’ internal perimeters. At the same time, they make it difficult for the latter to remain in public spaces in the immediate surroundings of blocos, even preventing them from moving about in those spaces.